2014
DOI: 10.1007/s00114-014-1205-z
|View full text |Cite
|
Sign up to set email alerts
|

Honeybee glucose oxidase—its expression in honeybee workers and comparative analyses of its content and H2O2-mediated antibacterial activity in natural honeys

Abstract: Antibacterial properties of honey largely depend on the accumulation of hydrogen peroxide (H2O2), which is generated by glucose oxidase (GOX)-mediated conversion of glucose in diluted honey. However, honeys exhibit considerable variation in their antibacterial activity. Therefore, the aim of the study was to identify the mechanism behind the variation in this activity and in the H2O2 content in honeys associated with the role of GOX in this process. Immunoblots and in situ hybridization analyses demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 27 publications
5
81
0
Order By: Relevance
“…According to our knowledge, there are no available literature reports that correlate evolved H 2 O 2 concentration with the glucose oxidase activity in honey. The only correlation reported is those by Bucekova et al (2014), who found that the amount of H 2 O 2 produced in honey solution could be correlated with the GOX levels. However, in this research authors examined the GOX levels in honey by immunobloting technique using a polyclonal antibody against the GOX, while hydrogen peroxide content in honeys diluted to 40 % of volume to volume ratio was determined after four hours of incubation at 37 °C.…”
Section: Resultsmentioning
confidence: 95%
“…According to our knowledge, there are no available literature reports that correlate evolved H 2 O 2 concentration with the glucose oxidase activity in honey. The only correlation reported is those by Bucekova et al (2014), who found that the amount of H 2 O 2 produced in honey solution could be correlated with the GOX levels. However, in this research authors examined the GOX levels in honey by immunobloting technique using a polyclonal antibody against the GOX, while hydrogen peroxide content in honeys diluted to 40 % of volume to volume ratio was determined after four hours of incubation at 37 °C.…”
Section: Resultsmentioning
confidence: 95%
“…Hydrogen peroxide is mainly produced during glucose oxidation catalysed by the bee enzyme glucose oxidase (GOX), which is introduced during nectar harvesting by bees (White et al, 1963). GOX is a regular honey component but its content varies significantly amongst different honeys (Bucekova et al, 2014). Furthermore, there is a positive correlation between the level of GOX in honey and the level of hydrogen peroxide in diluted honey.…”
Section: Introductionmentioning
confidence: 99%
“…We showed previously that the levels of another bee-derived protein, GOX, varied significantly among samples (Bucekova et al 2014). The variation in …”
Section: Discussionmentioning
confidence: 75%
“…The antibacterial efficacy of various honey samples was evaluated by the minimum inhibitory concentration (MIC) assay according to Bucekova et al (2014). Determination of MIC was conducted according to the recommendations of the Clinical and Laboratory Standards Institute (2003).…”
Section: Methodsmentioning
confidence: 99%